RACE AND POWER: EXPLOITATION AND RECONSTRUCTION OF HUMAN IDENTITY IN THE NOVEL, THE KNOWN WORD BY EDWARD P. JONES - Kashif Ahmad; Muhammad Bilal; Sajjad Ahmad; Saeed Ur Rahman; Anum Saleem (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
The study aims to explore class conflict as exploitation and reconstruction of human identity in the novel, The Known World. Slavery was a pervasive phenomenon in antiquity but it gradually declined in the modern world. These structural changes were aided by the blessings of modern moral attitudes and virtues. The study shows the reconstruction period which started in America followed by American Civil war, and it made a place of civil rights in the history of the United State. The research focuses on race and power: exploitation and reconstruction of human identity which indicates to a process in which an ex-slave used to buy other slaves when they got rid of slavery and came into power. They forgot about their past that how they spent life and faced with difficulties. But actually the trade of slave was legal and there was no restriction about it the trade of slave before civil war. As in the novel, The Known World (2003) the protagonist of this novel was once the slave of William Robbins and his whole family bound to Robbins but when they get rid of slavery so the protagonist plane to get power and dominate other. It is individual concept that land and money is the source of power and thus was a common practice among the masses which causes distraction.